Patient preferences in genetic newborn screening for rare diseases: study protocol - Martin, Sylvia; Angolini, Emanuele; Audi, Jennifer; Bertini, Enrico; Bruno, Lucia Pia; Coulter, Joshua; Ferlini, Alessandra; Fortunato, Fernanda; Frankova, Vera; Garnier, Nicolas; Grauman, Åsa; Gross, Edith; et al. (BMJ open, 2024)
INTRODUCTION: Rare diseases (RDs) collectively impact over 30 million people in Europe. Most individual conditions have a low prevalence which has resulted in a lack of research and expertise in this field, especially regarding genetic newborn screening (gNBS). There is increasing recognition of the importance of incorporating patients' needs and general public perspectives into the shared decision-making process regarding gNBS. This study is part of the Innovative Medicine Initiative project Screen4Care which aims at shortening the diagnostic journey for RDs by accelerating diagnosis for patients living with RDs through gNBS and the use of digital technologies, such as artificial intelligence and machine learning. Our objective will be to assess expecting parent's perspectives, attitudes and preferences regarding gNBS for RDs in Italy and Germany. METHODS AND ANALYSIS: A mixed method approach will assess perspectives, attitudes and preferences of (1) expecting parents seeking genetic consultation and (2) 'healthy' expecting parents from the general population in two countries (Germany and Italy). Focus groups and interviews using the nominal group technique and ranking exercises will be performed (qualitative phase). The results will inform the treatment of attributes to be assessed via a survey and a discrete choice experiment (DCE). The total recruitment sample will be 2084 participants (approximatively 1000 participants in each country for the online survey). A combination of thematic qualitative and logit-based quantitative approaches will be used to analyse the results of the study. ETHICS AND DISSEMINATION: This study has been approved by the Erlangen University Ethics Committee (22-246_1-B), the Freiburg University Ethics Committee (23-1005 S1-AV) and clinical centres in Italy (University of FerraraCE: 357/2023/Oss/AOUFe and Hospedale Bambino Gesu: No.2997 of 2 November 2023, Prot. No. _902) and approved for data storage and handling at the Uppsala University (2022-05806-01). The dissemination of the results will be ensured via scientific journal publication (open access).
Keywords: pacientova volba; novorozenecký screening; GENETICS; vzácné nemoci; Neonatal Screening; QUALITATIVE RESEARCH; Patient Preference; zjišťování skupinových postojů; Focus Groups; Patient-Centered Care; novorozenec; Artificial Intelligence; lidé; Patient Reported Outcome Measures; Humans; Patient Participation; Infant, Newborn; umělá inteligence; Rare Diseases